“THEY DO NOT WANT TO PAY RESPECT AND OBEDIENCE BECAUSE OF BEING A WOMAN ...”. CACICA AND JUDICIAL PRACTICES IN LAW SUITS ‘PUEBLOS DE INDIOS’. CENTRAL CHILE, LATE EIGHTEENTH CENTURY - Cerón Sandoval, Jeniffer (Revista de Historia Social y de las Mentalidades, 2016)
This article aims to reveal the role of some  women in the 'Indian peoples' of Central Chile  in the late eighteenth century. Through a case  of study, we propose an analysis of judicial  practices –or legal culture– by cacicas and  ‘indians’. In these particular cases, the ability of  these women had to defend themselves against  lawsuits that confronting their communities or  againts the landowners is enhaced.
Keywords: Justice; Practices; Cacicas; Communities